2018
DOI: 10.1007/s10006-018-0703-0
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide survey of undergraduate training in oral and maxillofacial surgery

Abstract: OMF surgery with its involvement both in medical and dental education has a special position as a surgical discipline. Our results show that OMF as a specialty is underrepresented in dental and especially in medical education considering the numerical and health economic importance of OMF consultations. Enhancing curricular integration and developing more structured examination forms is necessary to guarantee a high quality of OMF education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Clear positive information about OMFS care and careers should be present within the current dental and medical curricula. Where the curriculum is too full, this must be delivered with effective extra-curricula programmes ensuring that OMFS is not overshadowed by other specialties [ 17 , 18 ]. Consequently, for the field of OMFS, active involvement and collaborative design of educational content during the initial stages of training for both dental and, notably, medical students is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Clear positive information about OMFS care and careers should be present within the current dental and medical curricula. Where the curriculum is too full, this must be delivered with effective extra-curricula programmes ensuring that OMFS is not overshadowed by other specialties [ 17 , 18 ]. Consequently, for the field of OMFS, active involvement and collaborative design of educational content during the initial stages of training for both dental and, notably, medical students is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…The correct performance of a structured facial examination represents a fundamental basic clinical skill that is of great importance for the ongoing physician because of the high frequency of craniofacial trauma [30,31] especially since previous studies have shown signi cant shortcomings regarding Oral and Maxillofacial Surgery-related knowledge and skills in undergraduate education [32][33][34]. The aim of this study was to prospectively investigate the teaching e cacy of two teaching methods, namely a 'Mental Training' approach (study group) and the traditional 'See One, Do One' approach (control group) in the short-and long-term acquisition of the above-mentioned basic clinical skill.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only a few studies were carried in a controlled and curricular “in vivo” setting or focus on the long-term retention of the knowledge acquired [8, 9]. For Oral and Maxillofacial Surgery however, we were not able to find any study that met the aforementioned standards even though it is reported that VP are frequently (range 15 to 63%) used among dental schools [19, 20]. Most studies rather describe the technical development and feasibility of VP case creation [21] or investigate students’ perception and self-assessed learning progress using VP cases [11, 12, 22].…”
Section: Introductionmentioning
confidence: 99%